Anamnese, pathologische Originalbefunde, Therapie bezogene Parameter und Krankheitsverlauf: retrospektive Analyse von klinisch basierten Faktoren für die Prognose des tumorspezifischen Überlebens von 378 Patienten mit pT1-Harnblasenkarzinom - Breyer, J.; Otto, Wolfgang; Hartmann, Arndt; Bumes, B.; Bruendl, J.; Gierth, M.; Bertz, Simone; Denzinger, Stefan; Burger, M.; Lausenmeyer, E. M. (Aktuelle Urologie, 2015)
Urothelial carcinoma of the bladder (UBC) at stage pT1 is a heterogenous disease. Established criteria for prognosis prediction are not suitable for every patient. Choosing the right therapeutic strategy for the individual patient thus remains a challenge. The aim of the present study was to identify clinical parameters regarding cancer-specific survival (CSS) in patients with pT1 UBC.A retrospective analysis of clinical parameters of all patients with a pT1 UBC between 1989 and 2012 from a single centre was performed. Treatment consisted of transurethral resection, second resection followed by initially bladder sparing treatment. Anamnestic data, histopathological reports and clinical course were assessed with CSS being defined as primary endpoint. Kaplan-Meier analysis, uni- and multivariate analysis were performed using SPSS (Version 22, IBM).378 patients (78% male, median age 72 years) were included, median follow-up was 35 months. Pathological stage pT1G3 (66 vs. 91%, p<0.001), lack of instillation therapy (66 vs. 83%, p<0.001), presence of a second malignoma (41 vs. 77%, p=0,004), diagnosis after 2000 (75 vs. 76%, p=0,018) and tumour progress (42 vs. 85%, p<0.001) were associated with a worse CSS in univariate and Kaplan-Meier analysis. Multivariate analysis revealed the presence of a second malignoma (HR 2.267; CI 95% 1.143-4.497, p=0.019), pathological stage pT1G3 at initial diagnosis (HR 4.567; CI 95% 2.040-10.22, p<0.001) and tumour progress (HR 3.742; CI 95% 1.544-9.069, p=0.003) as independent negative predictors of CSS. Instillation therapy was a prognostic factor for improved CSS (HR 0.368; CI 95% 0.212-0.638, p<0.001).The present study identified the presence of a second malignoma, pathological stage pT1G3 and tumour progress as negative predictive factors for CSS. Maintenance instillation therapy after reresection was associated with an improved CSS.
EVALuna2:6722